Para-Sulphonato-calix[n]arenes as selective activators for the passage of molecules across the Caco-2 model intestinal membrane. Issue 45 (7th June 2015) - Roka, Eszter; Vecsernyes, Miklos; Bacskay, Ildiko; Félix, Caroline; Rhimi, Moez; Coleman, Anthony W.; Perret, Florent
<x xml:space="preserve">Abstract</x> The passage of Lucifer Yellow across the Caco-2 intestinal model membrane has been studied for the para-sulphonato-calix[n]arenes (CnS), the results show C4S and C8S activate membrane passage when used simultaneously with Lucifer Yellow, whereas C6S has no effect.